Enhancing Elementary Students’ Literacy Through a Mobile Learning Application - Rofi'i, Agus; Saputra, Dudu Suhandi; Yonanda, Devi Afriyuni; Lasmawan, I Wayan; Febriyanto, Budi; Yuliawati (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Low early reading skills among first-grade students are one of the fundamental problems in early literacy learning. The lack of engaging and interactive learning media causes students to be less motivated to develop basic reading skills. This study aims to analyze the effect of using mobile applications on improving students' early reading skills. This study is a quasi-experimental study with a Nonequivalent Control Group Design. The subjects of this study were first-grade students, with a total of 40 students consisting of 20 students in the experimental class and 20 students in the control class, determined through purposive sampling. Data collection was conducted using a preliminary reading skills test covering three indicators: letter recognition, word recognition, and reading words and sentences. The instrument used was a test sheet. Data analysis was conducted quantitatively using an Independent Sample T-test to compare pretest and posttest results between groups. The analysis results showed a significant difference between the experimental class and the control class, indicating that the use of mobile applications had a positive effect on early reading skills. The conclusion of this study is that mobile applications are effective as an alternative learning medium to improve students' early reading skills. The implications of this study suggest that the integration of technology in early reading learning can be an innovative solution in improving literacy quality in elementary schools.